2017
DOI: 10.1016/j.joca.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of persistent opioid use following hip or knee arthroplasty

Abstract: Objective The relationship between arthroplasty and long-term opioid use in patients with knee or hip osteoarthritis is not well studied. We examined the prevalence, patterns and predictors of persistent opioid use after hip or knee arthroplasty. Method Using claims data (2004–2013) from a U.S. commercial health plan, we identified adults who underwent hip or knee arthroplasty and filled ≥1 opioid prescription within 30 days after the surgery. We defined persistent opioid users as patients who filled ≥1 opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 29 publications
21
108
0
Order By: Relevance
“…Multiple demographic and clinical factors were associated with increased risk of chronic opioid use after hysterectomy, including older age, abdominal or laparoscopic/robotic hysterectomy, comorbidities, tobacco use, substance use disorders, certain pain conditions, and use of prescription psychiatric medication use (Table ). Our findings were consistent with other studies which showed that these factors increase the risk of chronic opioid use after major cardiac, thoracic, abdominal and pelvic procedures, or specific surgeries, including cesarean delivery, hysterectomy, hip or knee arthroplasty, spine, or bariatric surgeries . These findings underscore the importance of considering the individual patient's pain management needs; risk factors for opioid misuse at the time of opioid prescribing after hysterectomy and other surgical procedures; and importance of medical care, monitoring, and follow up postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple demographic and clinical factors were associated with increased risk of chronic opioid use after hysterectomy, including older age, abdominal or laparoscopic/robotic hysterectomy, comorbidities, tobacco use, substance use disorders, certain pain conditions, and use of prescription psychiatric medication use (Table ). Our findings were consistent with other studies which showed that these factors increase the risk of chronic opioid use after major cardiac, thoracic, abdominal and pelvic procedures, or specific surgeries, including cesarean delivery, hysterectomy, hip or knee arthroplasty, spine, or bariatric surgeries . These findings underscore the importance of considering the individual patient's pain management needs; risk factors for opioid misuse at the time of opioid prescribing after hysterectomy and other surgical procedures; and importance of medical care, monitoring, and follow up postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…The application of these definitions in the included studies was not always clear. Interestingly, one study took a data‐driven approach for LTOT definitions by using group‐based trajectory modeling, which identifies types of opioid use depending on changes in opioid use over time . Data‐driven approaches may improve the classification of LTOT, but studies have not compared the performance of data‐driven approaches to a simple, binary measures defined at prespecified time points.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study took a data-driven approach for LTOT definitions by using group-based trajectory modeling, which identifies types of opioid use depending on changes in opioid use over time. [55][56][57] Data-driven approaches may improve the classification of LTOT, but studies have not compared the performance of data-driven approaches to a simple, binary measures defined at prespecified time Only a handful of included studies used prescription characteristics to define LTOT, potentially reflecting a lack of guidance on using prescription characteristics, limited analytic resources, or belief that prescriptions characteristics do not improve the sensitivity of the measure. Existing guidance for researchers and health systems contains conflicting definitions for LTOT.…”
Section: /1002 = 57%mentioning
confidence: 99%
“…Conversely, our primary definition of persistent opioid use-or more restrictive definitions that have been used previously [43][44][45] -may risk understating the problem and cause some high-risk patients to be overlooked for interventions to prevent unnecessary persistent opioid use. However, it is notable that this wide variability in persistent opioid use prevalence across definitions of the measure could have implications for the perceived severity of the problem and effectiveness of interventions designed to prevent persistent opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…However, it identifies a larger subset of the population that initiates opioid therapy as persistent opioid users and may inflate the perceived severity of the problem at a population level and dissuade providers from prescribing opioid therapy when it is clinically appropriate. Conversely, our primary definition of persistent opioid use-or more restrictive definitions that have been used previously [43][44][45] -may risk understating the problem and cause some high-risk patients to be overlooked for interventions to prevent unnecessary persistent opioid use. Further work is needed to determine optimal strategies for identifying problematic persistent opioid use and how these measures should be tailored on the basis of pain indications and population characteristics.…”
Section: Discussionmentioning
confidence: 99%